The Effect of Aerobic and Anaerobic Exercise on Physical Fitness as Seen from the BMI of Chemical Engineering Students at the Veteran National Development University in Yogyakarta - Sumintarsih, Sumintarsih; Kurniati, Rizki; Mustofa, Hanafi; Trisaptono, Trisaptono (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2025)
This study aims to analyze the effect of exercise methods (aerobic and anaerobic) and Body Mass Index (BMI) categories on the improvement of physical fitness in students, measured through VO₂max, using a 2 × 2 quasi-factorial experimental design on 28 Chemical Engineering students at UPN Veteran Yogyakarta who took the Sports II course in volleyball. The results indicated that the aerobic exercise group with low BMI experienced the greatest increase in VO2max (3.94), while the anaerobic exercise group with high BMI recorded the smallest increase (2.27). The two-way ANOVA test showed that the exercise method did not have a significant effect on the increase in VO2max(F(calculated) 0.362 < F(table) 4.26), while the BMI factor had a significant effect (F(calculated) 6.392 > F(table) 4.26), where students with low BMI obtained higher increases than students with high BMI. The interaction test between exercise method and BMI was not significant (F(calculated) 0.021 < F(table) 4.26), indicating that both factors worked independently. Thus, it can be concluded that BMI status is a dominant factor in the increase in students' VO2max, while both aerobic and anaerobic exercise types are equally effective but not significantly different.